Course Notes on the Interpretation of Infrared and Raman Spectra - W. Mayo Dana (Wiley-Interscience, 2004)
Interpretation of IR and Raman Spectra provides the fundamentals of interpreting IR and Raman spectra of complex molecules primarily organic molecules. Examinations of theory provide a basis for predicting functional group frequency location in new molecular structures.